Creative pasts : historical memory and identity in western India, 1700-1960 - Deshpande, Prachi (Cultures of history., 2007)
The ""Maratha period"" of the seventeenth and eighteenth centuries, when an independent Maratha state successfully resisted the Mughals, is a defining era in the history of the region of Maharashtra in western India. In this book, Prachi Deshpande considers the importance of this period for a variety of political projects including anticolonial/Hindu nationalism and the non-Brahman movement, as well as popular debates throughout the nineteenth and twentieth centuries concerning the meaning of tradition, culture, and the experience of colonialism and modernity. Sampling from a ric